Pertanggungjawaban Pidana terhadap Penjual Obat Hexymer Tanpa Izin di Masyarakat - Natasya Simanjuntak; Immanuel Simanjuntak; Viona Sari Hasibuandan; Zico Ricardo Aritonang (CV Rewang Rencang, 2024)
Indonesia is a rule-of-law country that requires the law to be upheld, respected, and obeyed by everyone without exception. This includes the right of every individual to receive healthcare, which is guaranteed by the constitution and enforced in any country that adheres to this law to improve healthcare services for all its citizens and achieve its welfare goals. The rampant sale of drugs without a distribution license in society is concerning. One example is the widespread sale of drugs without approval from the National Agency of Drug and Food Control (BPOM), which poses a threat to public health and safety because there is no guarantee of safety from BPOM. This research uses normative legal research with a descriptive approach. The legal materials used include both primary and secondary legal sources. In this context, the author is interested in the criminal liability of individuals selling Hexymer without a license in society. The research questions are: What is the criminal responsibility of individuals selling Hexymer without a license in society? What are the judges' considerations in dealing with offenders who sell Hexymer without a license in society? Based on the findings, the author concludes that the criminal act of selling Hexymer without a license in society can be charged under Articles 196 and 197 of Law No. 36 of 2009 on Health, and in the judges' considerations, the offender may be subjected to a fine of IDR 5,000,000.